(untitled) (REMUNOM, 2025)
For millions of Brazilian students, water transportation for school children is not an option, but the only way to access school. This study analyzes the dynamics of water transportation for school children in riverside communities in the interior of the state of Amapá, focusing on the perceptions of users, the weaknesses of the service, and possible improvements to ensure safe and dignified access to education and social justice. Given this problem, it was felt that there was a need to discuss and democratize information that would allow for an understanding of the point of view of users and the agencies responsible for managing this transportation in the state. The methodology was based on a qualitative and quantitative approach, with the help of documentary research and on-site visits, to better understand the indicators obtained in the interviews involving students, parents, teachers, and technicians from schools that depend on this type of transportation. The results demonstrate, with regard to the implementation of public policies aimed at water transportation for school children, the need for decentralized strategies that consider the socio-territorial specificities of the different regions that depend on this type of transportation. This approach must recognize the unique characteristics of local contexts, valuing the institutional capacities of states and municipalities. Thus, the study reinforces the urgency of integrated public policies that consider the specificities of the Amazon and ensure that children and adolescents remain in school through decent, safe and regular transportation.